Radio Observations of Coronal Mass Ejection Initiation and Development in the Low Solar Corona - Carley, Eoin P.; Vilmer, Nicole; Vourlidas, Angelos (Frontiers in Astronomy and Space Sciences, 2020)
Coronal mass ejections are large eruptions of plasma and magnetic field from the low solar corona into the heliosphere. These eruptions are often associated with energetic electrons that produce various kinds of radio emission. However, there is ongoing investigation into exactly where, when and how the electron acceleration occurs during flaring and eruption, and how the associated radio emission can be exploited as a diagnostic of both the particle acceleration and CME eruptive physics. Here, we review past and present developments in radio observations of flaring and eruption, from the destabilisation of flux ropes to development of a CME and the eventual driving of shocks in the corona. We concentrate primarily on the progress made in CME radio physics in the past two decades, and show how radio imaging spectroscopy provides the ability to diagnose the locations and kinds of electron acceleration during eruption, which provides insight into CME eruptive models in the early stages of their evolution (<10 Rsun). We finally discuss how new instrumentation in the radio domain will pave the way for a deeper understanding of CME physics in the near future.